2022
DOI: 10.1021/acsapm.2c00080
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Bishelic[6]arene-Based Supramolecular Gels with Circularly Polarized Luminescence Property

Abstract: In this work, a pair of enantiomeric bishelic[6]­arenes (P / M-BH6) was synthesized and utilized to construct chiral supramolecular polymers with achiral luminescent guests through the host–guest interactions. The resulting linear supramolecular polymers could further self-assemble into supramolecular gels with enhanced emission. Moreover, the supramolecular gels with chiral and fluorescence properties exhibited circularly polarized luminescence (CPL) property induced by the chirality transfer from the chiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…Very recently, Chen's group 139 constructed linear supramolecular polymers by the assembling of a pair of enantiopure bishelic[6]arene derivatives P-/M - 137 and two fluorescent guests, G82 and G83 (Fig. 73).…”
Section: Applications Of Macrocyclic Arenesmentioning
confidence: 99%
“…Very recently, Chen's group 139 constructed linear supramolecular polymers by the assembling of a pair of enantiopure bishelic[6]arene derivatives P-/M - 137 and two fluorescent guests, G82 and G83 (Fig. 73).…”
Section: Applications Of Macrocyclic Arenesmentioning
confidence: 99%
“…For example, Guo et al recently reported a CPL-active supramolecular polymer system based on the host-guest complexation between chiral bishelic [6]arenes (P/M-BH6) and different achiral AIEgen guests. [90] As depicted in Figure 8A, a pair of amide group-bridged P/M-BH6 was synthesized as the chiral host, while blue-emissive AIEgen (BG) and yellow-emissive AIEgen (YG) with two trimethylammonium pendants were selected as the fluorescent guest molecules. With the increasing concentration of host-guest complex, uniform spherical particles and strips were suc-cessively observed, demonstrating the formation of linear supramolecular polymer chains via the host-guest interaction.…”
Section: Cpl-active Supramolecular Aie Polymers Based On Host-guest I...mentioning
confidence: 99%
“…(A-D)Reproduced with permission: Copyright 2022 American Chemical Society. [90] (E-G) Reproduced with permission: Copyright 2021 Wiley Online Library [91] (CB [8]) as the host macrocyclic molecule to interact with the AIEgen guest via head-to-tail host-guest complexation, an achiral supramolecular organic framework (SOF-1) can be generated. When L-/D-phenylalanine or a small amount of adenosine derivatives (ATP, ADP, and AMP) are encapsulated into the cavities of SOF-1, the achiral CB [8]-based supramolecular network polymer can be induced to show adaptive chirality (Figure 8F,G).…”
Section: Cpl-active Supramolecular Aie Polymers Based On Host-guest I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, aggregation-induced emission luminogens (AIEgens), which emit very weakly in dilute solution but become strongly emissive upon aggregation, have been developed into attractive building blocks to construct efficient solid-state CPL materials due to their intense fluorescence in the condensed state. Through the continuous efforts of researchers, CPL materials based on AIEgens, such as small organic molecules, polymers, liquid crystals, and supramolecular self-assemblies, have been reported. However, these CPL-active systems usually require tedious synthetic procedure or complicated preparation process, and moreover, the pure organic materials generally display low thermal stabilities.…”
Section: Introductionmentioning
confidence: 99%